POLITICAL-ECONOMY ACCOUNTING PERSPECTIVE: LANDASAN BARU PEMBERDAYAAN BUMN - Nur Fadjrih Asyik (InFestasi, 2010)
The investigation study the role of government in influencing the economy. Initially, economists acknowledge the role of government is only limited to the provision of social overhead capital or infrastructure to facilitate economic development, but subsequent developments bear the thought that emphasized the need for government intervention in the economy wider to solve certain problems (Krueger, 1990). There are several factors that indicate aspects of the general weakness of state enterprises such as production costs, efficiency, labor costs, capital costs, customer feedback, innovation and flexibility, decision making, continuity of service, cost control, and the relation of ownership, performance, and status organization. Relative Balance Theory of which is a pragmatic approach that skewness is determined by balancing the emphasis of environmental conditions. In relation to accounting, management of privatization and corporatization in the performance report on the management company in terms of accountability in the form of financial statements by considering the company's goals.